Design of a Combination of a Chopping Machine and Mobile Fermentation Tank for Cattle Breeders in Bone Regency - Fauzan Djamaluddin; Muhammad Syahid; Ilyas Renreng (Faculty of Engineering UNHAS, 2025)
Smallholder cattle farms in Sanrego Village, Kahu District, Bone Regency, face significant challenges related to the availability of green fodder, particularly during the dry season. To overcome this problem, the adoption of appropriate technology is essential to enhance feed processing efficiency and ensure a consistent supply of high-quality silage. This community service initiative was conducted under the Universitas Hasanuddin (UNHAS) Community Service Program in collaboration with partner institution CV. Reza. The program focused on the redesign of a mobile shredding machine integrated with a fermentation tank, developed to be more efficient, user-friendly, and aligned with the practical needs of local livestock farmers. The implementation process involved several stages, including problem identification, machine redesign, prototype development, user training, and mentoring for farmers. The results demonstrated that the redesigned machine effectively accelerated the shredding process, produced uniformly chopped green fodder, and facilitated efficient silage production. This technological innovation is expected to enhance farmer self-sufficiency, reduce feed production costs, and promote the sustainability of cattle farming enterprises in Bone Regency.